DEVOTIONAL POETRY IN TECHNICAL MANUSCRIPT TERMINOLOGY: AN INTRODUCTION TO THE ROSE GARDEN OF PURITY (GOLZĀR-E ṢAFĀ) - Amir H. Zekrgoo; Mandana Barkeshli, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2024)
Among the wide variety of Persian manuscript categories, there is a distinctive genre that includes recipes on materials and technics of manuscript production. And within this genre, we come across distinctly interesting works that adopt charming romantic poetry to record subjects that are rather dull, dry, and unattractive to the general audience! One of such historical sources is a sixteenth century manuscript entitled Rose Garden of Purity (Golzār-e Ṣafā) by ʿAlī Ṣayrafī, preserved in Paris Central Library. The subject of this research is the manuscript’s impressive Preface in which the poet expresses his sincere devotion to his Creator, and begs for forgiveness – all in melodious poetic language, using technical manuscript terms, colors and pigments as symbols and metaphors. The essay provides an opening remark entitled ‘Manuscripts on Manuscript Production’ followed by and introduction to the manuscript of ‘Golzār-e Ṣafā (Rose Garden of Purity). The little knowledge extracted about ʿAlī Ṣayrafī from the manuscript is shared under ‘The Author-cum-Poet.’ ‘Preface with 12 Couplets’ is the focal point of the essay; there the 12 couplets (24 hemistiches) are presented in the original language (Farsi/Persian) along with an English translation that is published here for the first time. A detailed analysis of technical terms used in the Preface, and an elaboration of their symbolic significance, is presented under ‘Expression of Devotion in Technical Manuscript Vocabulary.’